Targeting autophagy with natural products as a potential therapeutic approach for diabetic microangiopathy - Liu, Fengzhao; Zhao, Lijuan; Wu, Tao; Yu, Wenfei; Li, Jixin; Wang, Wenru; Huang, Chengcheng; Diao, Zhihao; Xu, Yunsheng (Frontiers in Pharmacology, 2024)
As the quality of life improves, the incidence of diabetes mellitus and its microvascular complications (DMC) continues to increase, posing a threat to people's health and well-being. Given the limitations of existing treatment, there is an urgent need for novel approaches to prevent and treat DMC. Autophagy, a pivotal mechanism governing metabolic regulation in organisms, facilitates the removal of dysfunctional proteins and organelles, thereby sustaining cellular homeostasis and energy generation. Anomalous states in pancreatic β-cells, podocytes, Müller cells, cardiomyocytes, and Schwann cells in DMC are closely linked to autophagic dysregulation. Natural products have the property of being multi-targeted and can affect autophagy and hence DMC progression in terms of nutrient perception, oxidative stress, endoplasmic reticulum stress, inflammation, and apoptosis. This review consolidates recent advancements in understanding DMC pathogenesis via autophagy and proposes novel perspectives on treating DMC by either stimulating or inhibiting autophagy using natural products.